2022
DOI: 10.3390/life12030365
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of the Elderly during the COVID-19 Pandemic in Asian Countries: A Cross-Sectional Study across Six Countries

Abstract: Background: Few studies have explored the determinants of health-related quality of life (HRQoL) in the elderly during the COVID-19 pandemic. Identifying these factors may help implement appropriate policies to enhance HRQoL in the elderly. Therefore, we aimed to identify the predictors of physical and mental component summary (PCS and MCS) scores of HRQoL in selected six low- and middle-income Asian countries. Methods: We conducted an online survey of older people aged ≥55 years in six countries: Bangladesh, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…Studies have unanimously agreed that COVID-19 has severe health repercussions, including quality of life ( 14 ), mental health ( 15 19 ), and psychological distress ( 20 25 ). Misinformation and vaccine efficacy also impacted the global COVID-19 vaccination program, driving vaccine hesitancy ( 26 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have unanimously agreed that COVID-19 has severe health repercussions, including quality of life ( 14 ), mental health ( 15 19 ), and psychological distress ( 20 25 ). Misinformation and vaccine efficacy also impacted the global COVID-19 vaccination program, driving vaccine hesitancy ( 26 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that the QoL in the entire cohort differed only marginally from the normal population, thus indicating that a substantial proportion of SARS-CoV-2-infections heal without long-term sequelae, in agreement with the results of several other studies [ 3 , 18 – 20 ]. We observed only a slight decrease in the role emotional dimension in the participants, possibly as a result of the general measures in managing the COVID-19 pandemic [ 21 ]. This finding is in line with the results of several other studies reporting a decline in QoL among COVID-19-survivors, depending on sociodemographic factors and belief in the negative effects of recent SARS-CoV-2-infection [ 22 ], which has also been observed in family members of ICU COVID-19-survivors [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…These measures were effective in reducing both transmission and the overall burden of COVID-19 disease (1). However, research has conclusively shown that COVID-19 has severe health effects including quality of life (2), mental health (3-7), and psychological distress (8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%